2002
DOI: 10.1093/aob/mcf047
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetic Analysis of Podocarpus and Comparison with Other Gymnosperm Species

Abstract: DNA sequences have been mapped to the chromosomes of Podocarpus species from New Zealand and Australia by fluorescent in situ hybridization. Unlike other conifers, these species show only one pair of major sites of 45S rDNA genes, and two additional minor sites were seen in the Australian P. lawrencei. Unusually, 45S sequences collocalize to the same chromosomal region as the 5S rDNA. The telomere probe (TTTAGGG)n hybridizes to the ends of all chromosomes as well as to a large number of small sites distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…Sone et al (1999) suggested that the insertion of 5S rDNA into 45S rDNA had taken place after the divergence from land plants because the co-localization of 5S and 45S rDNAs has been reported in some lower eukaryotes whereas not found in any spermatophytes. Thereafter, FISH analyses have revealed that a part or all of 5S rRNA loci in the chromosome complement co-localizes with 45S rRNA loci in a few species of spermatophytes, such as Podocarpus (Murray et al 2002), Ginkgo (Nakao et al 2005), Linum (Muravenko et al 2004), Rhoeo (Golczyk et al 2005), Hordeum (Taketa et al 2005) and Alstroemeria (Baeza et al 2007). In addition to the plant species, 120 Cytologia 74(2) H. Matoba and H. Uchiyama Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sone et al (1999) suggested that the insertion of 5S rDNA into 45S rDNA had taken place after the divergence from land plants because the co-localization of 5S and 45S rDNAs has been reported in some lower eukaryotes whereas not found in any spermatophytes. Thereafter, FISH analyses have revealed that a part or all of 5S rRNA loci in the chromosome complement co-localizes with 45S rRNA loci in a few species of spermatophytes, such as Podocarpus (Murray et al 2002), Ginkgo (Nakao et al 2005), Linum (Muravenko et al 2004), Rhoeo (Golczyk et al 2005), Hordeum (Taketa et al 2005) and Alstroemeria (Baeza et al 2007). In addition to the plant species, 120 Cytologia 74(2) H. Matoba and H. Uchiyama Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A group of monocotyledonous plants in the order Asparagales, forming a distinct clade in phylogenetic analysis, was reported previously to lack the ''typical'' Arabidopsis-type telomere repeat sequence (TTTAGGG) n (Fajkus et al 2005). the variability of the interstitial sites and copy number of the Arabidopsis-type telomeric sequences also seemed to be a characteristic of gymnosperms (Murray et al 2002). Schmidt et al (2000) analyzed the telomere repeats of conifers by Southern hybridization and showed that the low copy number of (CAC) 5 and (GACA) 4 in conifers and G. biloba L. was consistent with the data for angiosperms, which indicated that the structure of large conifer genomes and the organization of simple sequence repeats were to some extent similar to those of other, higher, plants.…”
Section: Introductionmentioning
confidence: 95%
“…Knowledge on conifer genomes, for instance, which have chromosome complements organized as metacentrics with similar sizes, was greatly increased by using rDNA FISH procedures (Hizume et al, 2002;Siljak-Yakovlev et al, 2002;Vischi et al, 2003;Cai et al, 2006). The rDNA loci have been localized in chromosomes of several gymnosperms species, for example, in members of the following families: Pinaceae, Podocarpaceae, and Cycadeceae (Tagashira and Kondo, 2001;Murray et al, 2002;Siljak-Yakovlev et al, 2002;Cai et al, 2006). The most studied genus until now has been Pinus , where comparison of karyotypes for 20 species revealed a great variation in the distribution of rDNA loci, especially the 45S rDNA, contrasting with other highly conserved genome characteristics as chromosome number and morphology (Cai et al, 2006).…”
Section: Rdna Sequences As Important Cytogenetic Toolsmentioning
confidence: 99%